2018
DOI: 10.1108/ijrdm-10-2017-0244
|View full text |Cite
|
Sign up to set email alerts
|

International franchising and performance: a resource-based perspective

Abstract: Purpose The purpose of this paper is to investigate international franchise performance. It focuses on how franchisors conceive their international performance, the drivers of their international performance, and how age-at-entry moderates the impact of their resources and capabilities (R&C) on international performance. Design/methodology/approach Using the lens of the resource-based view of the firm, the authors build on franchisor voice from a qualitative study (n=28) to propose a research model of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
(105 reference statements)
1
15
0
7
Order By: Relevance
“…Although TIP is a new element that we proposed within the EO dimension of innovativeness, innovativeness has previously been documented as having a positive impact on franchisee performance (Colla et al, 2019;Dada et al, 2015;Ghantous and Das, 2018). Thus, our finding is in consonance with the prior studies.…”
Section: Revisiting the Contingency Theorysupporting
confidence: 91%
“…Although TIP is a new element that we proposed within the EO dimension of innovativeness, innovativeness has previously been documented as having a positive impact on franchisee performance (Colla et al, 2019;Dada et al, 2015;Ghantous and Das, 2018). Thus, our finding is in consonance with the prior studies.…”
Section: Revisiting the Contingency Theorysupporting
confidence: 91%
“…Since franchisor performance depends on the success of franchisees, the former should effectively transfer knowledge to the latter for overall performance growth (Ghantous & Das, 2018). Knowledge transfer in international franchising is more complex than within countries due to institutional and cultural barriers between countries (Boh, Nguyen, & Xu, 2013;Ghantous & Das, 2018;Korbi & Chouki, 2017). Successful knowledge transfer has potential positive effects on chain performance.…”
Section: Knowledge Management In Franchisingmentioning
confidence: 99%
“…Likewise, Evanschitzky et al (2011) have shown that franchisee satisfaction influences customer satisfaction indirectly, through the satisfaction of the unit's employees, which favours customer loyalty. Therefore, healthy franchisor-franchisee relationships encourage the franchisee to make greater strides in consolidating the brand, enhancing market position (Nyadzayo et al, 2011;Ghantous and Das, 2018). On this basis, the following hypothesis is established: H5.…”
Section: Franchisor-franchisee Relationship Satisfaction and Customermentioning
confidence: 99%